Evaluasi Program Serasi (Selamatkan Rawa Sejahterakan Petani) di Desa Upang Makmur, Kecamatan Makarti Jaya Kabupaten Banyuasin - Dedy Sugianto; Sunarto Sunarto; Alamsyah Alamsyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Dedi Sugianto. Evaluation of the Serasi Program (Save the Prosperous Swamp of Farmers) in Upang Makmur Village, Makarti Jaya District, Banyuasin Regency. The objectives of this study are: 1) To describe and analyze the Evaluation of the Serasi Program (Save the Farmers Prosperous Swamp) in Upang Makmur Village, Makarti Jaya District, Banyuasin Regency; 2) To describe and analyze the supporting and inhibiting factors of the Serasi Program Evaluation (Save the Farmers Prosperous Swamp) in Upang Makmur Village, Makarti Jaya District, Banyuasin Regency. The results of the study stated that: 1) In the context, there are still many needs that have not been met in the implementation of the Serasi Program (Save the Prosperous Swamp of Farmers) in Upang Makmur Village, Makarti Jaya District, Banyuasin Regency. The condition of the embankment that is not too high, then the farmers are not compact in carrying out this program is a problem that must be solved immediately; From the input evaluation, it is known that the residents of Upang Makmur village as the implementer of the SERASI program have strong characteristics and a high commitment in making the SERASI program a success; Regarding the procedures in working, the residents of Upang Makmur village have followed all applicable rules; In the evaluation of the program, it can be concluded that the SERASI program in Upang Makmur Village has been implemented well, but not optimally, because there are still many things that must be improved in the future, so that the expected goals can really be maximally achieved. 2) The supporting factors in the Evaluation of the Serasi Program (Save the Prosperous Swamp of Farmers) in Upang Makmur Village, Makarti Jaya District, Banyuasin Regency are as adequate supporting infrastructure, the commitment and seriousness of the people of Upang Makmur Village in carrying out the program, the supervision carried out, and the clear program implementation procedures, the inhibiting factor is the condition of seawater that often enters agricultural land. The entry of seawater is also due to the condition of the embankment at several points that are not too high, so that seawater can enter agricultural land.